Glucocorticoids Alter CRTC-CREB Signaling in Muscle Cells: Impact on PGC-1α Expression and Atrophy Markers. - Jill A Rahnert; Bin Zheng; Matthew B Hudson; Myra E Woodworth-Hobbs; S Russ Price (PLoS ONE, 2016)
Muscle wasting associated with chronic diseases has been linked to decreased expression of PGC-1α and overexpression of PGC-1α counters muscle loss. CREB, in conjunction with the CREB-regulated transcription coactivator (CRTC2), is a positive modulator of PGC-1α transcription. We previously reported that PGC-1α expression is decreased in skeletal muscle of diabetic rats despite a high level of CREB phosphorylation (i.e., activation), suggesting that CRTC2-CREB signaling may be dysregulated. In this study, the relationship between CREB/CRTC signaling and PGC-1α expression was examined in L6 myotubes treated with dexamethasone (Dex, 48h) to induce atrophy. Dex decreased PGC-1α mRNA and protein as well as the levels of CRTC1 and CRTC2 in the nucleus. Dex also altered the nuclear levels of two known regulators of CRTC2 localization; the amount of calcinuerin catalytic A subunit (CnA) was decreased whereas SIK was increased. To assess PGC-1α transcription, muscle cells were transfected with a PGC-1α luciferase reporter plasmid (PGC-1α-Luc). Dex suppressed PGC-1α luciferase activity while both isobutylmethylxanthine (IBMX) and over-expression of CRTC1 or CRTC2 increased PGC-1α-Luc activity. Mutation of the CRE binding site from PGC-1α-Luc reporter attenuated the responses to both IBMX and the CRTC proteins. Consistent with the reporter gene results, overexpression of CRTC2 produced an increase in CRTC2 in the nucleus and in PGC-1α mRNA and PGC-1α protein. Overexpression of CRTC2 was not sufficient to prevent the decrease in PGC-1α mRNA or protein by Dex. In summary, these data suggest that attenuated CREB/CRTC signaling contributes to the decrease in PGC-1α expression during atrophy.